1972
DOI: 10.1002/dev.420050109
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation of the possible role of tactile and proprioceptive stimulation in certain aspects of embryonic behavior in the chick

Abstract: Tactile and proprioceptive stimulation designed to approximate natural sources of stimulation was administered to chick embryos from the 5th to the 16th day of incubation in the first 3 of 5 separate experiments. Such stimulation produced few modifications in the frequency, periodicity or qualitative aspects of embryos' movements at any age. In experiment IV, stimulation, considered to be atypical with regard to the frequency and intensity of administration, was found to modify the periodic but not the frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…To successfully hatch, the posture of the chick embryo must be oriented toward the top of the egg with the right side facing outward, thus providing a greater degree of mobility to the right side of the body. This mobility is needed as the chick rotates within the egg, breaking through the shell in a circular pattern as it moves (Freeman & Vince, 1974;Oppenheim, 1972). This right-side differential seems to be consistent throughout most of the late stages of incubation.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…To successfully hatch, the posture of the chick embryo must be oriented toward the top of the egg with the right side facing outward, thus providing a greater degree of mobility to the right side of the body. This mobility is needed as the chick rotates within the egg, breaking through the shell in a circular pattern as it moves (Freeman & Vince, 1974;Oppenheim, 1972). This right-side differential seems to be consistent throughout most of the late stages of incubation.…”
Section: Discussionmentioning
confidence: 80%
“…Oppenheim (1972) detailed the relatively invariant pattern of hatching behaviors required for a precocial bird to successfully escape the egg. Alternative positioning usually results in a failure to hatch and death inside the egg (see Asmundson, 1938 for analysis of failure to hatch rates).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we do not have a clear understanding of how sensory information modulates spontaneous embryonic movement. It has been shown that sensory synapses are present in the lumbosacral spinal cord as early as embryonic day (E) 7 in the chicken embryo (Lee et al, 1988; Davis et al, 1989) and that peripheral stimulation can initiate reflexic activity starting at this time (Oppenheim, 1972). Additionally, behavioral observations and manipulations have suggested that somatosensory feedback may be used to modify embryonic leg and wing motility as early as E9 (Bradley, 1997; Sharp et al, 1999).…”
mentioning
confidence: 99%
“…In fact, the organization of the neural circuitry precedes the time at which sensory input from leg afferents becomes available (Orr and Windle, 1934;Visintini and Levi-Montalcini, 1939;Oppenheim, 1972;Lee, Koebbe, and O'Donovan, 1988;Davis, Frank, Johnson, and Scott, 1989). Therefore, sensory feedback does not normally play a role in its initial development.…”
Section: Embryonic Motor Behavior In Chick Embryosmentioning
confidence: 99%